Perceived Overqualification at Work: Implications for Voice Toward Peers and Creative Performance - Li, Yi; Li, Yan; Yang, Peilin; Zhang, Man (Frontiers in Psychology, 2022)
Drawing on the conservation of resource theory, we examined the effect of perceived overqualification on the creative performance via voice toward peers, and how the peer-group perceived overqualification moderates the relationship between perceived overqualification and creative performance. We tested this proposal using three waves of lagged data collected from 206 company employees in Shandong Province, China. The results revealed that peer-group perceived overqualification moderated the indirect effects of perceived overqualification on creative performance such that there was positive indirect effect via voice toward peers when peer-group perceived overqualification is high and negative indirect effect via voice toward peers when peer-group perceived overqualification is low. The implications, limitations, and future directions of these findings were discussed.